Climate ambition steady: Urgency to act now trending up - Positive Energy; Nanos Research (Université d'Ottawa | University of Ottawa, 2021)
This (telephone and online) survey gauged views of 1000 Canadians on energy, climate change and the necessary ambition of mitigation policies. The survey updates measurements taken in June and November 2020. Results suggest Canadians’ climate ambition is holding steady during pandemic, but the sense of urgency to act appears to be trending up. This survey also asks Canadians how much they trust information about climate change from peer-reviewed science / researchers, traditional news media, NGOs, government agencies, politicians, industry and social media. Date: February 2021.
Keywords: Public confidence; Information; Energy Policy; Climate change; Canada; Climate change mitigation